Ritonavir-boosted danoprevir plus peginterferon alfa-2a and ribavirin in Asian chronic hepatitis C patients with or without cirrhosis - Jia Horng Kao (2018)
© 2016 Journal of Gastroenterology and Hepatology Foundation and John Wiley & Sons Australia, Ltd Background and Aim: Chronic hepatitis C is an important public health problem in Asia. We evaluated the safety, efficacy, and pharmacokinetics of fixed-dose ritonavir-boosted danoprevir plus peginterferon alfa-2a/ribavirin in treatment-naive Asian patients with chronic hepatitis C virus (HCV) genotype (G)1 infection. Methods: Treatment-naive G1 patients in Taiwan, Thailand, and Korea with serum HCV-RNA level ≥ 105IU/mL received ritonavir-boosted danoprevir 125/100 mg twice daily plus peginterferon alfa-2a/ribavirin for either 12 (noncirrhotic patients: Arm A, n = 34) or 24 weeks (cirrhotic patients: Arm B, n = 27) in this phase II open-label study. Sustained virologic response was defined as HCV-RNA < 25 IU/mL 12 weeks after end of treatment (SVR12). Results: Similar SVR12 rates were achieved in Arms A (88.2%; 95% confidence interval, 73.4–95.3%) and B (88.9%; 71.9–96.2%). Most patients had G1b infection, among whom SVR12 rates in Arms A and B were 96.7% and 91.7%, respectively. The overall SVR12 rate was 94.0% in noncirrhotic Taiwanese patients (100% in the subset of G1b patients). No patients withdrew for safety reasons. Three (11%) cirrhotic patients (Arm B) experienced serious adverse events, none of which was considered to be related to treatment. No Grade 3/4 alanine aminotransferase elevations were reported. The pharmacokinetic properties of danoprevir were broadly overlapping in noncirrhotic and cirrhotic patients both on Days 1 and 14. Conclusions: Ritonavir-boosted danoprevir plus peginterferon alfa-2a/ribavirin produced sustained virologic response rates > 90% after 12 weeks' treatment in noncirrhotic and 24 weeks' treatment in cirrhotic Asian patients with G1b infection and was well tolerated. These regimens are well suited to countries where G1b predominates.